Громадсько-просвітницький рух на Волині в 1918–1939 рр. - Філіпович, Мирослава; Filipovic, Miroslava (My University, 2016)
У статті розкрито роль інтелігенції в збереженні та розвитку культури у Волинському воєводстві в 1918− 1939 рр. Завдяки діяльності української інтелігенції волиняни зберегли власну самоідентифікацію, національну приналежність й отримали чималих культурних здобутків.This article explores the role of the intelligentsia in the preservation and development of culture in the Volyn province in the 1918-1939 biennium. Thanks to the activities of the Ukrainian intelligentsia Volhynians retained their identity, nationality and had a lot of cultural achievements. Reveals the formation and development of educational public organizations of the interwar period. Attention is paid to the activities of the active participants associations and their work, in particular I. Vlasovskogo, G. Zhezhko, M. Kalinchuka, G. Gladkogo, M. Levitskogo, O. Levchanivskoy, V. Ostrovskogo, G. Stepury, and other M. Cherkavskogo.
Socio-educational Movement in Volyn in 1918-1939 gg.
Keywords: Волинь; товариства; культура; інтелігенція; Volyn; society; culture; intelligence; education